Temperament and anxiety of children in childcare centre: child-parent relationship as mediator - Low, Biam Hong; Arshat, Zarinah; Yaacob, Siti Nor (Center for Promoting Ideas, 2018)
The present study was conducted to determine the relationships between child temperament and anxiety with child-parent relationship as mediator among children in childcare centers in Selangor, Malaysia. A total of 319 mothers with children aged between 3 to 6 years old were participated in the study. The findings revealed that both child’s sociability and close child-parent relationship had significant negative relationship with child’s anxiety symptom. Emotional children had significant higher levels of child’s anxiety symptom. Closeness child-parent relationship was fully mediated in child emotionality with anxiety and also child sociability with anxiety.